Future scenarios for oil palm mortality and infection by Phytophthora palmivora in Colombia, Ecuador and Brazil, extrapolated to Malaysia and Indonesia - Paterson, R. R. M. (2020)
Palm oil is a very important commodity especially to Malaysia and Indonesia. However, Latin American countries have significant industries, particularly Colombia. Climate change (CC) is a highly probable phenomenon which will affect diseases of oil palm (OP) with Phytophthora palmivora causing devastating outbreaks in Latin America and especially Colombia. Furthermore, the oomycete is an endemic pathogen to other crops in Malaysia such as durian, and is capable of causing disease of OP in vitro. A similar disease has been recorded in Thailand. It is crucial that P. palmivora is controlled in Malaysia and Indonesia because the organism is highly virulent, although there are acute and chronic forms. This current paper investigates the effect of CC on P. palmivora disease and on OP survival via a CLIMEX model for future suitable growth of OP. Postulated schemes are provided for Malaysia and Indonesia for acute and chronic forms of the disease which indicate an extremely high and increasing threat, likely to reduce the sustainability of the OP industry by 2050 and further by 2070 and/or 2100. Brazil appears less threatened by the disease under these scenarios, but their OP is likely to have 100% mortality. The chronic and acute forms of the malady present reduced and high threats respectively to Malaysia and Indonesia. The data herein will be useful for, inter alia, plantation managers who will be able to assess the accuracy of these scenarios in the future. Amelioration methods are required urgently and quarantine procedures need strengthening.